A Novel Treatment for Convex Lateral Crura: The Inverted Spanning Suture - Caropreso, Carlos Alberto; Porpino, Rafael; Neves, José Carlos; Ichiba, Gabriela; Hirotani, Paula; Carvalho, Victor; Souza, Maria Carolina; Rodrigues, José Luiz (Facial Plastic Surgery, 2024)
Rhinoplasty is one of the most complex and challenging procedures in plastic surgery, even for experienced surgeons. Among the steps leading to an aesthetic and functional nose, there is the nasal tip improvement. Today's approach to nasal tip is the product of different techniques shifting through time, mainly from a resection tendency, to preservation and suture use to reshape cartilages. Addressing the lateral crura is vital to an aesthetic nasal tip and it is frequently obtained by adequate suture techniques. The alar-spanning suture described by Perkins is one of such. Regardless of its importance, it was not able to improve convex crura in some cases. The inverted alar-spanning suture (ISS) is an adaptation designed to treat those cases with the suture alone. ISS is a novel technique that can lead to better results treating the convex lateral crura by distributing the force vector in a more effective way. New techniques in rhinoplasty have multiplied, bringing this procedure to a new level and keeping up with the updated notion of restoration instead of excision the ISS is a new, precise, approach to an old problem.
Keywords: alar-spanning suture; lateral crural spanning suture; nasal tip; rhinoplasty